Efektifitas Unit Intake, Aerasi, Pra-klorinasi, Koagulasi, Flokulasi di Instalasi Pengolahan Air (IPA) 2 Krian - Mustika Sari, Devi; Novirina Hendrasarie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to evaluate the effectiveness of water treatment process units including intake, aeration, pre-chlorination, coagulation, and flocculation at the Krian 2 Water Treatment Plant (IPA). Each unit has an important role in ensuring the quality of raw water into clean water that meets standards. The evaluation was carried out using a quantitative descriptive approach, using primary and secondary data obtained from field observations and laboratory tests. The results showed that the intake unit functioned quite well in supplying raw water with a stable discharge. The aeration unit was able to increase dissolved oxygen levels and reduce iron (Fe) and manganese (Mn) levels. The disinfection process showed effectiveness in reducing the number of pathogenic microorganisms, although it was influenced by the dose and contact time. The coagulation and flocculation units worked effectively in reducing turbidity and suspended solids through the addition of coagulant chemicals, namely PAC. Overall, the processing units at IPA 2 Krian have shown quite good effectiveness in producing clean water, although there are several technical aspects that need to be optimized to increase process efficiency.